2021
DOI: 10.1021/acs.energyfuels.1c01239
|View full text |Cite
|
Sign up to set email alerts
|

How Fast do Microdroplets Generated During Liquid–Liquid Phase Separation Move in a Confined 2D Space?

Abstract: How liquid transport occurs in confined spaces is relevant to many industrial and lab-scale processes, ranging from enhanced oil recovery to drug delivery systems. In this work, we investigate propelling microdroplets that form from liquid–liquid phase separation in a quasi-2D chamber, focusing on the direction and speed of microdroplets in response to local composition gradients. The confined ternary solution in our experiments comprises a model oil (the main one being octanol), a good solvent (ethanol), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In the study of the liquid-liquid separation, diffusive-dominated mixing causes the branch-like the structure of droplets, as shown in Figure [85], as shown in Figure 7(a). Arends et al [88,89] found a jetting phenomenon of the droplets, and the speed of the jetting was related to the composition of the solution. Meng et al [87] successfully applied the proposed…”
Section: Liquid-liquid Separation Via Ouzo Effect In Confined Spacesmentioning
confidence: 99%
“…In the study of the liquid-liquid separation, diffusive-dominated mixing causes the branch-like the structure of droplets, as shown in Figure [85], as shown in Figure 7(a). Arends et al [88,89] found a jetting phenomenon of the droplets, and the speed of the jetting was related to the composition of the solution. Meng et al [87] successfully applied the proposed…”
Section: Liquid-liquid Separation Via Ouzo Effect In Confined Spacesmentioning
confidence: 99%
“…In the study of the liquid–liquid separation, diffusive-dominated mixing causes the branch-like the structure of droplets, as shown in the figure, as shown in Figure a. Arends et al , found a jetting phenomenon of the droplets, and the speed of the jetting was related to the composition of the solution. Meng et al successfully applied the proposed quasi-2D chamber to the study of liquid–solid separation systems such as oiling-out crystallization, as shown in Figure b.…”
Section: Droplet Formation and Asphaltene Precipitation From Diffusiv...mentioning
confidence: 99%
“…These flows are not only set by the interaction between the different species and the gradient in composition, but also can be influenced strongly by the presence of solid surfaces and the wettability of each phase to the surface. For example, nucleated droplets may experience unidirectional propulsion due to Marangoni flow 27,29,30 set by a gradient in composition. Colloidal particles present in a phase separating mixture may experience phoretic motion, as the composition near the particle surface changes.…”
Section: Introductionmentioning
confidence: 99%